Acid leaching as efficient chemical treatment for rice husk in production of amorphous silica nanoparticles - Mahmud, A. (Asian Research Publishing Network, 2016)
High purity, high surface area silica nanoparticles could be produced from rice husk through chemical pre-treatment and combustion process. Acid leaching as efficient method of removing metallic impurities was employed during the chemical pre-treatment of rice husk prior to the burning process. In this paper, nano silica was generated from rice husk through citric and hydrochloric acids leaching by reflux boiling at 373K for 7200s so as to eliminate inorganic impurities and induce the hydrolysis of organic substances followed by burning at 973K of the residual solid husks from the leached husk. The generated silica nanoparticles were characterized to be of high purity (greater than 99) by X-ray Fluorescence (XRF) analysis in all the two acids treated husks. X-ray Photoelectron Spectroscopy (XPS) and Energy Dispersive Spectroscopy (EDS) confirmed this percentage purity as detection of negligible impurities. Brunauer Emmett Teller (BET) surface area of 234.6m2/g and 215.8m2/g with a pore diameter of 5.3nm and 5.5nm were obtained for hydrochloric and citric acids treated husks respectively, which proved the generated silica nanoparticles to be of high surface area. Danger is less with citric acid as compared to hydrochloric acid and with proven efficiency in removal of metallic impurities in rice husk and production of high purity silica, citric acid may be the best alternative. Â© 2006-2016 Asian Research Publishing Network (ARPN).